What Do We Mean by Sharing of Patient Data? DaSH: A Data Sharing Hierarchy of Privacy and Ethical Challenges - Schreiber, Richard; Koppel, Ross; Kaplan, Bonnie (Applied Clinical Informatics, 2024)
Background Clinical data sharing is common and necessary for patient care, research, public health, and innovation. However, the term “data sharing” is often ambiguous in its many facets and complexities—each of which involves ethical, legal, and social issues. To our knowledge, there is no extant hierarchy of data sharing that assesses these issues.Objective This study aimed to develop a hierarchy explicating the risks and ethical complexities of data sharing with a particular focus on patient data privacy.Methods We surveyed the available peer-reviewed and gray literature and with our combined extensive experience in bioethics and medical informatics, created this hierarchy.Results We present six ways on how data are shared and provide a tiered Data Sharing Hierarchy (DaSH) of risks, showing increasing threats to patients' privacy, clinicians, and organizations as one progresses up the hierarchy from data sharing for direct patient care, public health and safety, scientific research, commercial purposes, complex combinations of the preceding efforts, and among networked third parties. We offer recommendations to enhance the benefits of data sharing while mitigating risks and protecting patients' interests by improving consenting; developing better policies and procedures; clarifying, simplifying, and updating regulations to include all health-related data regardless of source; expanding the scope of bioethics for information technology; and increasing ongoing monitoring and research.Conclusion Data sharing, while essential for patient care, is increasingly complex, opaque, and perhaps perilous for patients, clinicians, and health care institutions. Risks increase with advances in technology and with more encompassing patient data from wearables and artificial intelligence database mining. Data sharing places responsibilities on all parties: patients, clinicians, researchers, educators, risk managers, attorneys, informaticists, bioethicists, institutions, and policymakers.
Keywords: health data sharing; ethical, legal and social issues; common rule; privacy; clinical and research data management; consent; HIPAA